2006
DOI: 10.1634/theoncologist.11-7-824
|View full text |Cite
|
Sign up to set email alerts
|

Primary (AL) Amyloidosis in Plasma Cell Disorders

Abstract: Primary (AL) amyloidosis is the most common form of systemic amyloidosis. The morbidity arises from extracellular deposition of immunoglobulin light chain (LC) fibrils in major organs, such as the kidneys, heart, and bowel. Organ dysfunction contributes to a high mortality and poor prognosis, with a median survival time of 1-2 years from diagnosis. Here, we present a 46-yearold man with an exceptional clinical course of an LC multiple myeloma with generalized amyloidosis, causing renal insufficiency, congestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
1
22
0
4
Order By: Relevance
“…Although bone marrow involvement by amyloid seems frequent in multiple myeloma, it is reported that less than 10% of the patients affected by MM may have or develop systemic AL amyloidosis [1]: this would suggest a lack of prognostic significance, but the influence of chemotherapy cannot be precisely weighed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although bone marrow involvement by amyloid seems frequent in multiple myeloma, it is reported that less than 10% of the patients affected by MM may have or develop systemic AL amyloidosis [1]: this would suggest a lack of prognostic significance, but the influence of chemotherapy cannot be precisely weighed.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary data available suggest that amyloid deposition in the marrow of myeloma patients is frequent, as it can be traced in nearly 40% of cases. We failed to find correlations between bone marrow amyloid deposits and immunoglobulin type, disease stage, plasma cells percentage, hemoglobin, calcium, creatinine, albumin, orIntroduction AL amyloidosis is the most frequent type of systemic amyloidosis in Western countries [1]. It is caused by tissueinfiltrating proteins derived from monoclonal immunoglobulin light chains, frequently observed in patients affected by multiple myeloma (MM) or, less frequently, by Waldenström's macroglobulinemia or other lymphoproliferative disorders [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ing V H , allowing its free secretion (9,10). The loss of the Ig heterotetrameric structure may contribute to the amyloidogenicity of light chain variable domains because the fibrils of most AL patients predominantly comprise a single variable domain (11).…”
mentioning
confidence: 99%
“…Amiloidozlar, anormal yapıda fibriler proteinlerin, çeşitli doku ve organlarda depolanarak o organın fonksiyonlarını bozmasıyla ortaya çıkan bir grup hastalıktır [36][37][38] . Amiloid fibrilleri farklı protein prekürsörlerinden köken alır ve proteolizise dirençlidir 39 .…”
Section: Amiloidozunclassified